Product Photography and Digital Content Strategies for Strengthening Digital Business - Shinta Abdul Rahman; Pahri Pahri; Citra Meylana Rina Jayanti (Sean Institute, 2026)
The rapid growth of the digital economy has encouraged micro and small enterprises to adopt digital platforms for marketing and business development. However, many digital businesses still face challenges in presenting products effectively due to limited visual quality and unstructured digital content strategies. This study aims to analyze the role of product photography in improving product visual quality and to identify effective digital content strategies that strengthen digital business performance and competitiveness. The research employed a qualitative approach using secondary data derived from 30 relevant scientific articles related to digital marketing, visual communication, and digital entrepreneurship. The collected literature was analyzed using qualitative content analysis to identify conceptual patterns linking visual presentation, consumer perception, digital engagement, and marketing outcomes. The findings reveal three main results. First, high-quality product photography significantly improves visual perception and increases perceived product value in digital marketplaces. Second, professional product images enhance consumer trust and stimulate higher engagement through increased attention and interaction with digital content. Third, structured digital content strategies such as engaging visual content, targeted messaging, and active consumer interaction expand online visibility and improve brand performance. These findings indicate that the integration of professional product photography and strategic digital content management functions as a key mechanism for strengthening consumer engagement, increasing purchasing intentions, and improving the competitiveness of digital businesses. Therefore, visual marketing and well-structured digital communication strategies are essential components for supporting sustainable digital business development.